SYNTAX score as predictor of adverse events in patients after acute myocardial infarction - Davidović Aleksandar; Davidović Jelica; Đorđević Marina; Resimić Radmila; Otašević Dijana; Lazić Snežana; Lazić Bratislav; Cvijanović Dane (Association of Nurses Technicians and Midwives, 2021)
Introduction: Acute coronary syndrome manifests as STEMI and NSTEMI acute myocardial infarction (AIM). Adverse cardiovascular events include: heart failure, nonfatal reinfarction, recurrent angio pain, rehospitalization, and mortality. The SYNTAX score is an angiographic indicator that is a predictor of adverse events after AIM. The aim of this study was to determine the significance of Syntax score as a predictor of adverse outcomes in patients after acute myocardial infarction. Method: A retrospective study was conducted at the Zvezdara Clinical Hospital in Belgrade in the Department of Interventional Cardiology, by analyzing medical documentation for the period January - March 2020. 80 patients of both sexes, aged 30 to 80, were examined and hospitalized for myocardial infarction. The monitored parameters were: socioepidemiological data, SYNTAX score, adverse events (recurrent infarction, revascularization, stroke and mortality). Results: Of the 80 respondents included in the study, 32.5% were female and 67.5% male. 75% of them had STEMI and 25% NSTEMI entity. The average age of the patients was 61.7 years. Adverse events one year after hospitalization were present in 40% of patients with STEMI, namely: reinfarction in 6.7%, revascularization in 23.3%, stroke in 1.7% and lethal outcome in 8.3% of patients. SYNTAX score is low in 24 patients (40%) with STEMI myocardial infarction and high SYNTAX score in 25 subjects (41.6%). Conclusion: The SYNTAX score as a predictor of adverse outcomes is extremely important for clinical practice and follow-up of patients after acute myocardial infarction.